Bufalin reverses ABCB1-mediated resistance to docetaxel in breast cancer. Issue 3 (March 2023) - Zhang, Die; Jia, Tingting; Chen, Xingxing; Jiang, Haopeng; Guo, Teng; Dong, Junjun; Zeng, Hairong; Wang, Yixin; Yuan, Yi
Abstract: Background: Docetaxel (DCT) is widely used in clinical practice, but the drug resistance of breast cancer patients has become an important reason to limit its clinical efficacy. Chan'su is a commonly used traditional Chinese medicine for the treatment of breast cancer. Bufalin (BUF) is a bioactive polyhydroxy steroid extracted from chan'su and has strong antitumor activity, but there are few studies on reversing drug resistance in breast cancer. The aim of this study is to determine whether BUF can reverse the drug resistance to DCT and restore efficacy in breast cancer. Methodology: The reversal index of BUF was detected by Cell Counting Kit-8 (CCK-8) assays. The effects of BUF on enhancing the apoptosis of DCT were detected by flow cytometry and Western Blot (WB), and the main differential expression levels of sensitive and resistant strains were detected by high-throughput sequencing. Rhodamine 123 assay, WB and ATP Binding Cassette Subfamily B Member 1 (ABCB1) ATPase activity experiments were used to detect the effect of BUF on ABCB1. The nude mouse orthotopic model was constructed to investigate the reversal effect of BUF on DCT resistance in vivo . Results: With BUF intervention, the sensitivity of drug-resistant cell lines to DCT was increased. BUF can inhibit the expression of ABCB1 protein, increase the drug accumulation of DCT in drug-resistant strains, and reduce the ATPase activity of ABCB1. Animal experiments show that BUF can inhibit the growth of drug-resistant tumors in an orthotopic model of breast cancer and decrease the expression of ABCB1. Conclusion: BUF can reverse ABCB1-mediated docetaxel resistance in breast cancer.